Access to and Documentation of Publicly Financed Survey Data - Wolfgang Jagodzinski; Christof Wolf (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The topic of this paper is access to and documentation of survey data financed through public funds. We distinguish between four types of publicly financed survey data: (1) Academic survey data from the national or international research infrastructures; (2) data from DFG projects or similarly funded projects; (3) survey data collected in research projects funded by the Federal State and the Länder (Ressortforschung); (4) Population and Household surveys from national and international statistical agencies. For each of these types of data we describe the current situation and present recommendations for future developments.
Keywords: 330; Survey data; data access; data documentation; data archive